Sleep and subjective cognitive decline in cognitively healthy elderly: Results from two cohorts. (25th September 2018) - Tsapanou, Angeliki; Vlachos, Georgios S.; Cosentino, Stephanie; Gu, Yian; Manly, Jennifer J.; Brickman, Adam M.; Schupf, Nicole; Zimmerman, Molly E.; Yannakoulia, Mary; Kosmidis, Mary H.; Dardiotis, Efthimios; Hadjigeorgiou, Georgios; et al.
Abstract: Subjective cognitive decline may reflect a dementia prodrome or modifiable risk factor such as sleep disturbance. What is the association between sleep and subjective cognitive decline? Cross‐sectional design, from two studies of older adults: the WHICAP in the USA and the HELIAD in Greece. A total of 1, 576 WHICAP and 1, 456 HELIAD participants, without mild cognitive impairment, dementia or severe depression/anxiety, were included. Participants were mostly women, with 12 (WHICAP) and 8 (HELIAD) mean years of education. Sleep problems were estimated using the Sleep Scale from the Medical Outcomes Study. Subjective cognitive decline was assessed using a structured complaint questionnaire that queries for subjective memory and other cognitive symptoms. Multinomial or logistic regression models were used to examine whether sleep problems were associated with complaints about general cognition, memory, naming, orientation and calculations. Age, sex, education, sleep medication, use of medications affecting cognition, co‐morbidities, depression and anxiety were used as co‐variates. Objective cognition was also estimated by summarizing neuropsychological performance into composite z ‐scores. Sleep problems were associated with two or more complaints: WHICAP: β   = 1.93 (95% confidence interval: 1.59–2.34), p  ≤ .0001; HELIAD: β   = 1.48 (95% confidence interval: 1.20–1.83), p  ≤ .0001. Sleep problems were associated with complaints in all the cognitive subcategories, except orientation for the WHICAP. The associations were noted regardless of objective cognition. At any given level of objective cognition, sleep disturbance is accompanied by subjective cognitive impairment. The replicability in two ethnically, genetically and culturally different cohorts adds validity to our results. The results have implications for the correlates, and potential aetiology of subjective cognitive decline, which should be considered in the assessment and treatment of older adults with cognitive complaints.